Survey and molecular characterization of pathogens in wild Amazon parrot nestlings and recently seized nestlings from ilegal trade - Vaz, Frederico Fontanelli (2020)
Birds of the order Psittaciformes are among the most threatened birds in Brazil. Of the 86 species recorded, 24 (27.9%) are in the International Union for Conservation of Nature Red List. Amazon parrots have a highlight for being among the most trafficked birds, especially the blue-fronted Amazon parrot (Amazona aestiva). The red-tailed Amazon parrot (A. brasiliensis) is in the near threatened category and the red-spectacled Amazon parrot (A. pretrei) is threatened in the vulnerable category, both of them needing management in the wild. In addition to habitat loss and illegal trade, the spread of pathogens is an emerging threat to these species due to their wide movement, trade and manipulation. Considering the lack of information on the health of wild parrots, the aims of this study were to investigate selected pathogens on wild A. aestiva, A. brasiliensis and A. pretrei nestlings and in A. aestiva seized from illegal trade. Samples from 235 wild Amazon parrots were collected in four Brazilian states, and samples from 90 A. aestiva were collected from nestlings seized from illegal trade and submitted to a Wildlife Rehabilitation Center (CRAS). Samples were tested by PCR for Chlamydia psittaci, Psittacid alphaherpesvirus 1, poxvirus and Beak and feather disease virus (BFDV). Chlamydia psittaci DNA was detected in swab samples from five wild nestlings. The DNA of the other pathogens was not detected in the wild and trafficked bird samples. Sequencing of C. psittaci in the sample of one A. brasiliensis revealed high similarity with isolates found in parrots in Brazil, belonging to genotype A. The results of the present study demonstrate that the prevalence of pathogens in wild parrots is very low, and exotic pathogens such as BFDV may not yet have reached these populations, although they are present in captivity in Brazil. This reinforces the need to protect our bird fauna from imminent threats of introducing and spreading these viruses into the wild. Novel health assessment protocols should be discussed and strictly followed for the reintroduction of parrots in the wild. Regarding the birds from CRAS, they were isolated and sampled soon after their arrival at the center, and were not monitored to evaluate long-term effects of captivity on their health. Preventive measures should never be neglected in psittacine birds introduced in a flock, as studies reveal outbreaks and the detection of relevant pathogens to the conservation of these birds. Further studies should be encouraged to better understand the epidemiology of pathogens in wild parrots, to expand the knowledge of their impacts on species conservation.